2022
DOI: 10.3390/ijms23105443
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9–Mediated Genome Editing for Pseudomonas fulva, a Novel Pseudomonas Species with Clinical, Animal, and Plant–Associated Isolates

Abstract: As one of the most widespread groups of Gram–negative bacteria, Pseudomonas bacteria are prevalent in almost all natural environments, where they have developed intimate associations with plants and animals. Pseudomonas fulva is a novel species of Pseudomonas with clinical, animal, and plant–associated isolates, closely related to human and animal health, plant growth, and bioremediation. Although genetic manipulations have been proven as powerful tools for understanding bacterial biological and biochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The off-target effects are commonly due to PAM and sgRNA mismatches. Currently, various bioinformatics tools have been developed to help predict and reduce off-target modifications ( Zhang et al, 2022 ). In this study, the potential off-target sites of CRISPR/Cas9 were predicted through 12 nucleotide sequences of sgRNA and PAM sites by aligning the sgRNA sequences with reference genome sequences using Tbtools software to search mismatch.…”
Section: Resultsmentioning
confidence: 99%
“…The off-target effects are commonly due to PAM and sgRNA mismatches. Currently, various bioinformatics tools have been developed to help predict and reduce off-target modifications ( Zhang et al, 2022 ). In this study, the potential off-target sites of CRISPR/Cas9 were predicted through 12 nucleotide sequences of sgRNA and PAM sites by aligning the sgRNA sequences with reference genome sequences using Tbtools software to search mismatch.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Ralstonia is an important inflammatory factor in the intestine. [27][28][29][30][31][32] The study further showed that the abundance of Pseudomonas and Ralstonia in the R group was significantly higher than in the T group (p<0.05). We speculate that the composition of tilapia intestinal flora in the rice-fish symbiosis mode is more conducive to fish health.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pseudomonas strains have an established role in the biotechnology field ( 26–28 ), their potential could be enhanced by further exploiting their unique traits and improving our ability to modify them using genetically engineering ( 29–31 ). Although improving intrinsic lifestyle characteristics such as tolerance, handling, growth and substrate consumption rates remains challenging, the incredible progress of genetic engineering during the last decades sets the stage for efficient tailoring of microbial metabolism for a large array of bioconversions, including, for example, the assimilation of non-canonical nutrients and C1 compounds.…”
Section: Introductionmentioning
confidence: 99%